Redesigning Healthcare Waqf: Key Characteristics and Strategic Models for Indonesia Using the Delphi–Likert Approach - Sulistyowati, Sulistyowati; Ascarya, Ascarya; Sukmana, Raditya; Astarudin, Tatang; Napitupulu, Rodame Monitorir (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2025)
This study explores the essential characteristics of healthcare waqf and proposes context-appropriate models for implementation in Indonesia. Employing the Delphi method alongside a Likert scale, expert consensus validated 23 out of 31 proposed characteristics, with significant agreement indicated by Kendall’s W. The identified healthcare waqf types include clinics, general hospitals, children’s hospitals, and specialist hospitals. These institutions can be financed through a blend of Islamic social and commercial finance and managed by a subsidiary, third party, or nāẓir (waqf manager). Based on these characteristics, four models are proposed: social, simple productive, innovative productive, and integrated social-productive healthcare waqf models. These models aim to provide accessible healthcare services for both underserved populations and the general public. While designed for Indonesia, the study’s methodological approach and conceptual framework can be adapted for application in other contexts. This research offers a novel foundation for developing effective, sustainable healthcare waqf initiatives.